ANALYSIS OF ROAD DAMAGE LEVEL BASED ON THE INDEKS KONDISI PERKERASAN METHOD ON THE MOJOKERTO-JOMBANG ROAD SECTION - Lestari, Indri; Raharjo, Nain Dhaniarti; Sholeh, Moch. (Jurnal Online Skripsi Manajemen Rekayasa Konstruksi (JOS-MRK), 2023)
Mojokerto-Jombang Road section is a national road that connects the main use areas in Mojokerto and has a high vehicle intensity. This damage to the road caused the decrease in quality and disturb in comfort of road users. Therefore this study aims to analyze the level of damage, provide handling, and find out the Cost Budget Plan needed for handling the damage. The calculation method used Indeks Kondisi Perkerasan Method (IKP). The primary data in this study is visual damage condition survey, while the secondary data are average daily traffic data, road technical data, CBR data, and PUPR 2022 unit prices. The results of the study are road damage Patching by approximately 41,8%, Edge Cracking around 4,3%, Potholes by approximately 8,9%, Aligator Cracking around 33,7%, Block Alligator by approximately 4,6%, Bleeding around 0,6%, Longitudinal Cracking by approximately 5,2%, Polished Aggregate around 0,5%, and Rutting by approximately 0,3% with a pavement surface condition value a 19,4% Good, 14,2% Satisfactory, 20,1% Fair, 17,2% Poor, 11,9% Very Poor, 14,9% Serious, and 2,2% Failed. On the other hand, the types of handling in this study obtained Routine Maintenance 19%, Periodic Maintenance 14%, Rehabilitation 19%, and Reconstruction/ Recycling 47%. The budget estimate plan for all repair works is about Rp. 63,562,961,000,-.